Industrial Strategy, Embeddedness and Performance of Canting Seal Industry in Pekalongan, Indonesia - Retnaningsih, Tri Kurniawati; Lestari, Etty Puji; Basir, Moh. Abdul (Advances in Social Sciences Research Journal, 2017)
Canting seal industry is a supportiing of batik industry. From the number of quantity of canting cap industry is little bit and concentrated in the area of large batik industry such as pekalongan, Indonesia. This article analyzes the competitiveness of industry in Pekalongan canting seal using SWOT analysis. SWOT analysis is an acronym for strengths, weaknesses, opportunities and threats and is a structured planning method that evaluates reviews those elements of an organization, project or business venture. The results showed that the strength of the industry is relatively large canting seal. Their cheap labor costs and high quality raw materials provide their own advantages in this industry also. Thus the results of the resulting product quality is also good. The sale price is competitive also provides its own strength in this industry cluster. Currently canting seal craftsmen are in one cluster to facilitate the supply of raw materials.